2014
DOI: 10.1089/biores.2014.0036
|View full text |Cite
|
Sign up to set email alerts
|

Constitution of Fibrin-Based Niche for In Vitro Differentiation of Adipose-Derived Mesenchymal Stem Cells to Keratinocytes

Abstract: Epithelialization of chronic cutaneous wound is troublesome and may require use of skin/cell substitutes. Adipose-derived mesenchymal stem cells (ADMSCs) have immense potential as autologous cell source for treating wounds; they can cross the germ layer boundary of differentiation and regenerate skin. When multipotent adult stem cells are considered for skin regeneration, lineage committed keratinocytes may be beneficial to prevent undesirable post-transplantation outcome. This study hypothesized that ADMSCs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
0
21
0
3
Order By: Relevance
“…[23][24][25] For better regenerative potential and mechanical stability, fibrin matrices have been combined with other biological or synthetic molecules, eg, collagen, 26,27 hyaluronic acid with a cell adhesion-promoting peptide, 28 basic FGF, 29 or EGF. 30 Fibrin has relatively rarely been deposited on supporting substrates, although fibrin selfsupporting matrices are usually fragile. In our previous study, we deposited a fibrin nanocoating on polylactide nanofibrous membranes and observed its positive influence on the behavior of dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] For better regenerative potential and mechanical stability, fibrin matrices have been combined with other biological or synthetic molecules, eg, collagen, 26,27 hyaluronic acid with a cell adhesion-promoting peptide, 28 basic FGF, 29 or EGF. 30 Fibrin has relatively rarely been deposited on supporting substrates, although fibrin selfsupporting matrices are usually fragile. In our previous study, we deposited a fibrin nanocoating on polylactide nanofibrous membranes and observed its positive influence on the behavior of dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…46,76 When ADSCs are grown in vitro on a scaffold containing adhesion molecules and growth factors found in PRP, they show increased differentiation to keratinocytes suggesting an enhanced benefit to wound healing. 79 It has also been shown in vitro that a majority of platelets remain active at 10 days when cocultured with ADSCs indicating a bilateral prosurvival relationship that may enhance healing potential. 80 PRP has anti-inflammatory properties that may reduce the inflammation and swelling, which encourage degeneration of the fat graft.…”
Section: The Role Of Prp In Fat Graft Survivalmentioning
confidence: 99%
“…PRP also contains cell adhesion molecules including fibronectin and vitronectin, which help to immobilise growth factors within the fibrin and help the fibrin scaffold act as a matrix for epithelial migration . When ADSCs are grown in vitro on a scaffold containing adhesion molecules and growth factors found in PRP, they show increased differentiation to keratinocytes suggesting an enhanced benefit to wound healing . It has also been shown in vitro that a majority of platelets remain active at 10 days when cocultured with ADSCs indicating a bilateral prosurvival relationship that may enhance healing potential …”
Section: The Role Of Prp In Fat Graft Survivalmentioning
confidence: 99%
“…Human ADSCs can be converted to epithelial cells expressing the characteristics of cytokeratins 5, 14, 19, and α 6; integrins; and even desmoglein 3 [ 60 , 61 ]. They can also differentiate into fibroblast cells, demonstrating not only their morphological similarity but also their ability to also express cell surface proteins including vimentin and fibronectin [ 60 ].…”
Section: Chronic Woundsmentioning
confidence: 99%